NEW INSIGHT ON EPIDEMIOLOGY AND MANAGEMENT OF BACTERIAL BLOODSTREAM INFECTION IN PATIENTS WITH HEMATOLOGICAL MALIGNACIES - Sara Lo Menzo; Giulia la Martire; Giancarlo Ceccarelli; Mario Venditti (Mediterranean Journal of Hematology and Infectious Diseases)
Bloodstream infections (BSI) are an important cause of morbidity and mortality in onco-hematologic patients. The Gram-negative etiology was the main responsible of the febrile neutropenia in the sixties and its impact declined due to the use of fluoroquinolone prophylaxis; this situation was followed by the gradual emergence of Gram-positive bacteria also following of the increased use of intravascular devices and the introduction of new chemotherapeutic strategies. In the last decade the Gram-negative etiology is raising again because of the emergence of resistant strains that make questionable the usefulness of currentstrategies for prophylaxis and empirical treatment. Gram-negative BSI attributable mortality is relevant and the appropriate empirical treatment significantly improves the prognosis; on the other hand the delayed adequate treatment of Gram-positive BSI does not seem to have an high impact on survival. The clinician has to be aware of the epidemiology of his institution and of colonizations of his patients in order to choose the most appropriate empiric therapy. Ina setting of high endemicity of multidrug-resistant infections, even the choice of a targeted therapy can be a challenge, often requiring strategies based on off-label prescriptions and low grade evidences.